Free radical nanocopolymerization in AAO porous materials: Kinetic, copolymer composition and monomer reactivity ratios. (16th August 2021) - León-Boigues, Laia; Navarro, Rodrigo; Mijangos, Carmen
Abstract: Free radical (FR) polymerization in non-interconnected nanochannels of anodic aluminum oxide templates (AAO) represents a suitable and less energetic method to prepare supported hierarchical polymer nanostructures when compared to the main alternative which is through polymer melt infiltration. Nevertheless, FR copolymerization has not been studied in the nanoscopic templates even if it is of great interest to produce a wide variety of polymeric materials with modulated properties. In this work, we explore the ability to copolymerize butyl methacrylate (BMA) and 2-hydroxyethyl acrylate (HEA) monomers in lab-made Anodic Aluminum Oxide (AAO) nanoreactors. Thus, P(BMA/HEA) copolymer has been successfully synthesized to a 100% conversion degree within AAO geometries at relatively low temperatures in 90 min. The reaction of copolymerization in confinement showed faster polymerization rates than bulk copolymerization. 1 H NMR allowed to follow monomer conversion in the AAO nanoreactor for a wide range of monomer compositions, from 0 to 100% whereas differential scanning calorimetry (DSC) was employed to quickly observe the overall kinetics of the copolymerization reaction. At conversion degrees <20%, the reactivity ratios of BMA and HEA monomers was determined and this was related to the distribution of the monomers on the P(BMA/HEA) copolymer synthesized in confinement and bulk. HEA is the most reactive monomer in the copolymerization reaction in confinement and in bulk, however, in the restricted geometry of AAO template, the reactivity ratios shift slightly away from the preferential incorporation of HEA. Finally, SEM images of P(BMA/HEA) copolymer nanofibers extracted from the AAO nanoreactor showed an homogeneous and ordered nanostructured morphology. Since copolymer nanostructures are composed of monomers that combine interesting softening properties with a high swelling capacity, the nanostructured copolymer could be of special interest to surface science studies and specifically for coatings applications. Graphical abstract: Image 1 Highlights: Free radical copolymerization of acrylic monomers was performed in AAO templates. A 100% of copolymerization conversion is achieved in 90 min in soft conditions. Monomer reactivity ratios of acrylic monomers was determined by 1 H NMR. Copolymerization kinetics was determined by DSC and 1 H NMR. The nanostructured copolymers are suitable for coating applications.